2017
DOI: 10.1111/ejn.13748
|View full text |Cite
|
Sign up to set email alerts
|

The neural oscillations of speech processing and language comprehension: state of the art and emerging mechanisms

Abstract: Neural oscillations subserve a broad range of functions in speech processing and language comprehension. On the one hand, speech contains-somewhat-repetitive trains of air pressure bursts that occur at three dominant amplitude modulation frequencies, physically marking the linguistically meaningful progressions of phonemes, syllables and intonational phrase boundaries. To these acoustic events, neural oscillations of isomorphous operating frequencies are thought to synchronise, presumably resulting in an impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
291
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(309 citation statements)
references
References 212 publications
(332 reference statements)
15
291
3
Order By: Relevance
“…Interestingly, gamma oscillations are thought to reflect the active maintenance of object representations in memory in infants (Kaufman, Csibra, & Johnson, ) and have been linked in adults to both attention (Müller, Gruber, & Keil, ; Ray, Niebur, Hsaio, Sinai, & Crone, ) and language (e.g., Pulvermüller et al., ). Specifically, the gamma range is likely to be implicated in the important early building blocks of linguistic representations—phonemic perception (Meyer, ). Clearly more than an ability to discriminate between phonemes is required to successfully segment continuous speech, which requires the infant to identify syllables and the relationships between them.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, gamma oscillations are thought to reflect the active maintenance of object representations in memory in infants (Kaufman, Csibra, & Johnson, ) and have been linked in adults to both attention (Müller, Gruber, & Keil, ; Ray, Niebur, Hsaio, Sinai, & Crone, ) and language (e.g., Pulvermüller et al., ). Specifically, the gamma range is likely to be implicated in the important early building blocks of linguistic representations—phonemic perception (Meyer, ). Clearly more than an ability to discriminate between phonemes is required to successfully segment continuous speech, which requires the infant to identify syllables and the relationships between them.…”
Section: Discussionmentioning
confidence: 99%
“…Both alpha and delta oscillations are less well studied in sentence comprehension, but an early proposal suggested that alpha may have a task‐specific working memory function (Bastiaansen & Hagoort, ). A recent proposal makes this idea more concrete by claiming that during sentence comprehension, alpha plays a key role in the inhibition of competing or task‐irrelevant information in short‐term memory (Meyer, ). These ideas are compatible with the more general role of alpha in working memory mentioned earlier.…”
Section: Theories Of Neural Oscillationsmentioning
confidence: 99%
“…These ideas are compatible with the more general role of alpha in working memory mentioned earlier. Finally, Meyer () also discusses a role for delta oscillations in chunking information into phrasal units during sentence comprehension with this chunking being driven by intonational phrase boundaries early in development and with a gradual switch to reliance on internal constraints generated by developing knowledge of linguistic structure (see Meyer, , for a more comprehensive discussion of how to reconcile delta entrainment to bottom‐up information available in speech with its sensitivity to abstract syntactic structure).…”
Section: Theories Of Neural Oscillationsmentioning
confidence: 99%
See 2 more Smart Citations